Comparative study using Portland cement and calcium carbide residue as a promoter in bottom ash geopolymer mortar. (15th February 2017) - Hanjitsuwan, Sakonwan; Phoo-ngernkham, Tanakorn; Damrongwiriyanupap, Nattapong
Highlights: Sustainable masonry units using waste materials. Role of calcium promoter on strength development of BA geopolymer. PC provided more reaction products and degree of geopolymerization than CCR. Both PC and CCR replacement met the strength requirement for masonry units. Abstract: This article presents the comparative study using Portland cement (PC) and calcium carbide residue (CCR) as a promoter on properties of bottom ash (BA) geopolymer cured at ambient temperature. Two calcium promoters: PC and CCR were used to replace BA at the amount of 10%, 20%, and 30% by weight of binder. Sodium hydroxide and sodium silicate solutions were used as liquid alkaline activation in all mixtures. The setting time and strength development of BA geopolymer mortars were studied. XRD, SEM and FTIR analyses were used on the BA geopolymer pastes with calcium promoters for investigating the reaction products. The results showed that the use of calcium promoters to replace BA resulted in decreasing of setting time whereas its strength development enhanced. The highest compressive strength of BA geopolymer mortars could be observed at the BA replacement with 30% of PC and 30% of CCR which were 13.8 and 11.4 MPa, respectively. The difference in strength development of BA geopolymer mortars with calcium promoters was due to degree of geopolymerization. The results of XRD, SEM and FTIR analyses agreed well with strength behaviors that the use of PC provided more reaction products and degree of geopolymerization than that of CCR. The 28-day compressive strengths of both PC and CCR replacement met the strength requirement for non-load-bearing and load-bearing brick masonry units as specified by ASTM standard. In addition, the outcome of this research could help divert significant quantity of waste materials from landfills and considerably reduce environmental damage caused by carbon emissions due to PC production.